Lexical Features of Teacher Talk in English Classrooms in Senior High Schools - Irmayani, Irmayani; Rachmajanti, Sri (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
AbstractEnglish as a Foreign Language (EFL) in Indonesia has been taught since elementary schools. As the only setting for EFL learners to learn English formally, the students of Senior High Schools are in the 7th to 9th year in acquiring English as a foreign language. As non-native English teachers who has been teaching English for years, English teachers in Indonesia are supposed to be the source of language input for learners. This article explores lexical features of teacher talk as an input in EFL classrooms in 8th year of senior high schools of English language classrooms. Type token ratio and parts of speech as some particular modified input of teacher talk are used to see lexical density in English classrooms. This study was conducted by descriptive method with qualitative approach. The data of the present study were taken from classroom observations equipped with audio recordings. The result revealed the variants of type token ratio among the teachers and lexical variety that teachers’ oral input. The variety of lexical features of teacher talk from will be discussed to examine type token ration, lexical density and proportion of the use of nouns and verbs.(176 words)